Effects of the micro–nano surface topography of titanium alloy on the biological responses of osteoblast. Issue 3 (18th November 2016) - Yin, Chengcheng; Zhang, Yanjing; Cai, Qing; Li, Baosheng; Yang, Hua; Wang, Heling; Qi, Hua; Zhou, Yanmin; Meng, Weiyan
Abstract: In clinical applications, osseointegration is essential for the long‐term stability of dental implants. Inspired by the hierarchical structure of natural bone, we applied the electrochemical etching (EC) technique to form a micro–nano structure on a titanium alloy (Ti6Al4V) substrate, called EC surface. Sand blasting and acid etching (SLA) and machined (M) methods were employed to generate micro and smooth textures, respectively, as the control groups. The surface topographies of the three substrates were characterized using scanning electron microscopy (SEM). Then, human osteoblast‐like cells (MG63) were cultured on substrates, and adhesion, proliferation, morphology, alkaline phosphatase activity (ALP), and gene expression levels of Runt‐related transcription factor 2 (RUNX2), osteocalcin (OCN), osteopontin (OPN), and type I collagen (COLIA 1) were analyzed. MG63 cells cultured on the EC Ti alloy substrates displayed better cell adhesion, significant proliferation, and a higher production level of ALP, gene expressions of RUNX2, OCN, OPN and COLIA 1 ( p < 0.01 or p < 0.05) compared with those of SLA and M substrates. These results indicate that the micro–nano structure fabricated by electrochemical etching method is beneficial for the biological functions of MG63 cells and may be a promising candidate in dental implants. © 2016 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 105A: 757–769, 2017.